TINJAUAN ARTIKEL : UJI MIKROBIOLOGI - Nurul, Ahsana; Setiawan, Iwan; Yusa, Delia; Trisna, Dhea; Halisa, Nur; Putri, Odilia; Ekawati, Oktavia; Umi, Yuliana; Ze Fanya (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2023)
Microorganisms such as bacteria are one of the causes of disease that many patients suffer. Bacteria can easily reach food or pharmaceutical preparations during the production process, so it is important to carry out antibacterial testing on a product to ensure product safety and quality. The activity of an antibacterial can be observed by several methods such as diffusion, dilution and broth microdilution. The purpose of this article review is to provide information regarding microbiological tests that can be used to test antibacterial activity. The method used is an online search for international journal literature using online search sites such as Google schoolar, Pubmed and Scopus. Various studies have found, it is known that the antibacterial activity test consists of three types. The first diffusion method consisting of a diffusion disc and wells. The purpose of the diffusion method is to determine the sensitivity and resistance of a bacterium to antibiotics. The two dilution methods consist of solid dilution and liquid dilution. The purpose of the dilution method is to determine the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MBC). The effective microdilution of the three broths was used to determine the Minimum Inhibitory Concentration (MIC) and Minimum Kill Concentration (MBC). In the antibacterial activity test a bacterial inhibition zone will appear which will be measured according to the results. The size of the diameter of the inhibition zone will increase with increasing concentration of antibiotics.